Cetak Biru Pelayanan Pasien di Rumah Sakit Jiwa Provinsi Jawa Barat Tahun 2014 - Yulianti, Yuyun (UI Scholars Hub, 2015)
The in-patient refusal number in West Java Province Psychiatric Hospital which reach 300-400 patient per year(1), doesn’t go along with the hospital achievement number in 2013. This research is aimed to describe a Service-Blueprints for inpatients services and investigate potential points for improvement by observings five service units that are involved. This is a qualitative research with operational research technique. The results are a set of service-blueprints design for outpatients or emergency patients, who need hospitalization, and establishing the use of Positive and Negative Syndrome Scale-Excited Component (PANSS-EC) instrument as a tool for determining the patient status can significantly lower patient refusal.